Combination of Metformin and Magnesium Citrate Reduces TNF-α, NF-κB p65, IL-6, CD4, and MMP-9 Expressions in Diabetic Model Rats - Rachmi Fauziah Rahayu; Adi Prayitno; Bambang Purwanto; Widiastuti Soewondo; Ida Nurwati; Eti Poncorini Pamungkasari; Paramasari Dirgahayu (Indonesian Biomedical Journal)
BACKGROUND: Diabetes, which causes various complications, involves pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), nuclear factor kappa B p65 (NF-κB p65), interleukin-6 (IL-6), cluster of differentiation 4 (CD4), and matrix metalloproteinase-9 (MMP-9). Magnesium has demonstrated anti-diabetic properties, but its anti-inflammatory effects in preventing cardiovascular complications remain unclear. This study aimed to evaluate the anti-inflammatory effects of magnesium citrate, alone and in combination with metformin, by measuring TNF-α, NF-κB p65, IL-6, CD4, and MMP-9 expression in diabetic model rats.